Desbaste na cultura do feijoeiro-comum - de S Figueiredo, Matosinho; Vieira, Clibas (Revista Ceres, 2025)
A study was conducted in Viçosa, Minas Gerais, Brazil, comparing the following times for thinning field beans (Phaseolus vulgaris): 6, 12, 18, and24days after seedling emergence. The variety ’Rico-23’, with a vegetative cycle of 90 days, was used. Results indicated no differences between treatments for yield and final stand.